The Promise for Histone Methyltransferase Inhibitors for Epigenetic Therapy in Clinical Oncology: A Narrative Review - Rugo, Hope S.; Jacobs, Ira; Sharma, Shikhar; Scappaticci, Frank; Paul, Thomas A.; Jensen-Pergakes, Kristen; Malouf, Gabriel G. (Advances in therapy, 2020)
Epigenetic processes are essential for normal development and the maintenance of tissue-specific gene expression in mammals. Changes in gene expression and malignant cellular transformation can result from disruption of epigenetic mechanisms, and global disruption in the epigenetic landscape is a key feature of cancer. The study of epigenetics in cancer has revealed that human cancer cells harbor both genetic alterations and epigenetic abnormalities that interplay at all stages of cancer development. Unlike genetic mutations, epigenetic aberrations are potentially reversible through epigenetic therapy, providing a therapeutically relevant treatment option. Histone methyltransferase inhibitors are emerging as an epigenetic therapy approach with great promise in the field of clinical oncology. The recent accelerated approval of the enhancer of zeste homolog 2 (EZH2; also known as histone-lysine N -methyltransferase EZH2) inhibitor tazemetostat for metastatic or locally advanced epithelioid sarcoma marks the first approval of such a compound for the treatment of cancer. Many other histone methyltransferase inhibitors are currently in development, some of which are being tested in clinical studies. This review focuses on histone methyltransferase inhibitors, highlighting their potential in the treatment of cancer. We also discuss the role for such epigenetic drugs in overcoming epigenetically driven drug resistance mechanisms, and their value in combination with other therapeutic approaches such as immunotherapy.